2001
DOI: 10.1161/01.atv.21.6.997
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Neutralizing Antibodies Against Platelet-Derived Growth Factor-AA Inhibit Atherogenesis in the Cholesterol-Fed Rabbit

Abstract: Abstract-Previous studies have shown that the B chain of platelet-derived growth factor (PDGF) has an important role in atherogenesis. In this study we have investigated the contribution of PDGF-A chain in cholesterol-induced atherogenesis in the New Zealand White rabbit. High titers of antibodies to PDGF-AA or to platelet cytosolic protein (PCP) were induced in these animals by immunization against recombinant human PDGF-AA or human PCP. Rabbits were then fed a 0.25% to 1% cholesterol-containing diet for 10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…12 Recent studies suggest that an overactivated PDGF system may play a role in the development of atherosclerosis in the context of hyperlipidemia. [13][14][15][16] The role of PDGF in atherosclerosis in the diabetic context remains unknown. This area of research has been hampered by a lack of an appropriate animal model.…”
Section: See Page 801mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Recent studies suggest that an overactivated PDGF system may play a role in the development of atherosclerosis in the context of hyperlipidemia. [13][14][15][16] The role of PDGF in atherosclerosis in the diabetic context remains unknown. This area of research has been hampered by a lack of an appropriate animal model.…”
Section: See Page 801mentioning
confidence: 99%
“…Specifically, clinical and experimental studies have shown that PDGF has a role in the development of atherosclerosis in the context of hyperlipidemia. [13][14][15][16] PDGF-A and PDGF-B mRNA levels are increased in circulating mononuclear cells of hypercholesterolemic and hyperlipidemic patients. 13 In rabbits fed with a high-cholesterol diet, immunization against PDGF-AA 14 or against PDGF-BB 15 reduces the size of aortic atherosclerotic lesions.…”
Section: Lassila Et Al Imatinib and Diabetic Atherosclerosis 939mentioning
confidence: 99%
“…PDGF has long been recognized as a powerful VSMC mitogen [3] and the induction of PDGF receptors in VSMCs during atherogenesis has been demonstrated in several studies [4,5]. Blockade of PDGF, whether by anti-PDGF antibody [6][7][8], PDGF receptor antisense therapy [9,10], or chimeric knockout in mice [11], reduces lesion formation after vascular injury. Ligand binding to the PDGF receptor causes tyrosine autophosphorylation and Address correspondence to: Kathy K. Griendling, Emory University, Division of Cardiology, 319 WMB, 1639 Pierce Dr., Atlanta, GA 30322,, e-mail: kgriend@emory.edu.…”
mentioning
confidence: 99%
“…23 Protracted lesion formation requires a prolonged period of treatment and poses problems for experimental investigation, particularly with the administration of blocking antibodies. Studies in which endogenous neutralizing antibodies were induced in rabbits before initiation of the atherosclerotic diet 24,25 and PDGF receptor antibodies were administered long term in the ApoE null mouse model of atherosclerosis 26 have suggested the possibility that blockade of PDGF or the PDGF ␤-receptor can reduce lesion size. In this study, we have examined lesions in detail in ApoE Ϫ/Ϫ mice at extended time points and used two different approaches to test the role of PDGF in SMC accumulation in advanced lesions of atherosclerosis: hematopoietic chimeras lacking PDGF-B in their circulating cells and mice treated daily with a PDGF receptor antagonist.…”
mentioning
confidence: 99%
“…Our results contrast with recent reports from two groups that blockade of PDGF can decrease the size of lesions of atherosclerosis. 24 -26 In the rabbit studies, in which endogenous antibodies were induced by immunization with either PDGF-AA 25 or PDGF-BB, 24 lesions were evaluated 12 to 18 weeks after initiation of a 1% cholesterol diet. Lesion area evaluated by oil red O staining of the entire aorta shows a decrease of approximately 30%, and cross-sectional quantitation of aortic lesion-media ratios at a single site suggests up to 95% reduction.…”
mentioning
confidence: 99%